Extracting oil from used auto tires at low temperature after chemical treatment. (March 2017) - Kandah, Munther; Al-Otoom, Awni; Al-Harahsheh, Mohammad; Al-Zoubi, Raed M.; Al-Harahsheh, Adnan
Highlights: Chemical treatment followed by low temperature solvent extraction for used tires was performed. Chemical treatment by sodium carbonate was found to affect the sulphur content in the extracted oil. The best solvent was found to be a mixture of acetone (50%) and hexane (50%). The solvent extraction oil yield from tires after chemical treatment was 30% at optimum conditions. Abstract: This study presents an alternative tactic to pyrolysis of auto tires avoiding the use of high temperature and increasing the yield of oil produced. It depends on a simple chemical treatment of auto tires with sodium carbonate at low temperature (50 °C) followed by solvent extraction. This treatment produced two folds of the yield that can be obtained using normal solvent extraction. The experimental results suggests that sodium carbonate is responsible for breakage of CS bond in the main structure of auto tires making solvent extraction easier. Additionally, the sulphur content of the extracted oil using the sodium carbonate treatment is reduced significantly (by about 28%) making the product more favorable energy/fuel source. This technique allows about 30 wt.% of oil to be extracted from the used auto tires at 50 °C under atmospheric pressure resulted from the breakage of the sulphur cross-linking by the sodium carbonate.